Disturbance rejection approaches of Korteweg–de Vries-Burgers equation under event-triggering mechanism - Kang, Wen; Zhang, Jing; Wang, Jun-Min (Automatica (Oxford), 2024)
In this paper, disturbance rejection approaches are suggested to stabilize Korteweg–de Vries–Burgers (KdVB) equation under the averaged measurements. Here two approaches—active disturbance rejection control (ADRC) and disturbance observer-based control (DOBC), are introduced to reject the external unknown disturbance actively. The main challenging issue is to design the effective extended state observer (ESO)/disturbance observer (DO) for KdVB equation respectively. As for ADRC strategy, the disturbance is rejected on the basis of an ESO. As for DOBC strategy, a DO is constructed to estimate the disturbance formulated by an exogenous system. Continuous-time and event-triggered anti-disturbance controllers are further presented for distributed stabilization of KdVB system. To significantly reduce the amount of control updates, an event-triggering mechanism is utilized and the Zeno behaviour is avoided. Sufficient stability conditions are established via Lyapunov functional method. The effectiveness of proposed approaches is verified by simulation results.